On the periodic nature of some max-type difference equations - E. M. Elabbasy; H. El-Metwally; E. M. Elsayed (International Journal of Mathematics and Mathematical Sciences)
We study some qualitative behavior of solutions of some max-type difference equations with periodic coefficients. Some new results of the periodicity character of solutions of that type of difference equations will be established.